Risk of Multidrug Resistant Bacteria Acquisition in Patients with Declared β-Lactam Allergy during Hospitalization in Intensive Care Unit: A Retrospective Cohort Study (2007-2018) - Alessio Strazzulla; Maria Concetta Postorino; Nabil Belfeki; Laura Iordache; Astrid de Pontfarcy; Aurelia Pitsch; Pierre Leroy; Sebastien Jochmans; Mehran Monchi; Sylvain Diamantis (Journal of Immunology Research)
Introduction. The risk of extended spectrum β-lactamase (ESBL) bacterial acquisition in patients with β-lactam allergy has been poorly investigated. In a previous study conducted over a 6-year long period (2007-2012), we found that patients with declared β-lactam allergy had a higher risk of ESBL bacterial carriage at admission in intensive care unit (ICU), but they had not a higher risk of ESBL bacterial acquisition. We present the final results of the study which was eventually conducted over a 12-year long period (2007-2018). Materials and Methods. The study included all patients admitted in ICU and receiving antibiotic treatment from January 2007 to December 2018. ESBL bacterial acquisition was the main clinical outcome. Mortality in ICU, multidrug resistant bacterial carriage at admission and discharge were the secondary outcomes. Results. Overall, 3332 patients were included, 132/3332 (3.9%) were labelled β-lactam allergic, while 3200/3332 (96.1%) did not presented β-lactam allergy. No significant difference in rates of ESBL acquisition was detected (4/132, 3% vs. 78/3200, 2.4%; p=0.17). Patients with β-lactam allergy had higher rates of ESBL bacterial carriage at admission (19/132, 14.4% vs. 248/3200, 7.8%, p=0.01) and at discharge (22/132, 16.7% vs. 351/3200, 11%, p=0.04) than nonallergic patients. No differences in mortality, duration of hospitalization, and carriage of methicillin resistant Staphylococcus aureus were reported. Female gender was the only factor associated with β-lactam allergy at the multivariate analysis. Conclusions. This study confirms that patients with declared β-lactam allergy had not a higher risk of ESBL bacterial acquisition during hospitalization in ICU. However, they had a higher ESBL bacterial carriage at admission.